JARINGAN INTELEKTUAL MUDA MUHAMMADIYAH (JIMM) AND THE IDEOLOGY OF PROGRESSIVE ISLAM: Construction, Genealogy, and Current Development (State Islamic University (UIN) of Sunan Ampel Surabaya, 2024)
This article aims to investigate the ideology of progressive Islam of the Muhammadiyah Young Intellectuals Network (JIMM), a progressive wing within Muhammadiyah. This provides a systematic discussion of the construction of the JIMM’s ideology, its genealogy, and its current development. This is primarily based on the qualitative data purposively collected through participatory observation and interviews, conducted mainly during the 2023 JIMM Congress in Yogyakarta. By employing a sociology of knowledge approach, this article finds that the progressive idea of JIMM is deeply rooted in and has a coherence with Muhammadiyah, particularly in Ahmad Dahlan’s ideology of progressive Islam which combines religious liberalisation and social liberation as embodied in the Al-Ma’un Theology and the Alleviation of Public Misery. We argue that in its recent evolution, JIMM’s ideology of progressive Islam has responded to various contemporary issues, as demonstrated by its activists who have proposed to focus more on the advocacy for human rights, gender justice, religious harmony, universal access to education, environmental stewardship, and caderisation.